Adsorption of anionic azo dyes using lignite coke by one-step short-time pyrolysis. (1st May 2020) - He, Qiongqiong; Wang, Guoqiang; Chen, Zishan; Miao, Zhenyong; Wan, Keji; Huang, Shaomeng
Graphical abstract: Highlights: Lignite cokes by one-step short-time pyrolysis were used for dyes removal. Lignite cokes exhibited high removal efficiency for most dyes. Hydrophobic adsorption and large surface area devoted to high adsorption performance. Abstract: Textile wastewater is among the top three major industrial wastewaters in China and efforts have been made by both the government and industry to develop a low-cost treatment process. In this study, lignite cokes (LCs) prepared by one-step low, medium, and high temperature pyrolysis were used for the removal of four anionic azo dyes. The adsorption efficiency of LCs increased when heated to a temperature higher than 700 °C for a period of time longer than 5 min; this improvement in the adsorption efficiency weakened for temperature higher than 700 °C. The heating of LCs for 5 min was commonly adopted for industrial adsorbents preparation, which considered both processing costs and the adsorption efficiency. The LC treatment at 700 °C for 5 min (LC-700-5) could remove more than 95% of Congo red (CR), methyl orange (MO), and direct fast blue B2RL (DB) dye. Excellent dye removal efficiency was observed for LC-900-5, in which more than 99% of CR, MO, and DB and 89.8% of direct yellow brown D3G were removed. The oxygen-containing groups of LCs decomposed, and its micropores and macropores were substantially developed to form a honeycomb porous structure with a significantly larger surface area. The combination of hydrophobic adsorption, large surface area, and rich macropores and micropores contributed to the high adsorption performance of LCs obtained at high temperatures. Therefore, LCs obtained by one-step short-time medium or high-temperature pyrolysis in this study could be used as effective adsorbents for dyes, which demonstrated potentially significant environmental, social, and economic benefits.